The enabling environment for informal food traders in Nigeria’s secondary cities - Resnick, Danielle; Sivasubramanian, Bhavna; Idiong, Idiong Christopher; Ojo, Michael Akindele; Tanko, Likita (International Food Policy Research Institute, 2018)
Informal vendors are a critical source of food security for urban residents in African cities. However, the livelihoods of these traders and the governance constraints they encounter are not well-understood outside of the region’s capital and primate cities. This study focuses on two distinct secondary cities in Nigeria, Calabar in the South-South geopolitical zone of the country and Minna in the Middle Belt region. Local and state officials in each city were interviewed on the legal, institutional, and oversight functions they provide within the informal food sector. This was complemented with a survey of 1,097 traders across the two cities to assess their demographic characteristics, contributions to local food security, key challenges they face for profitability, engagement with government actors, and degree of access to services in the markets.